Pendampingan Pengelolaan Sampah Di Bank Sampah Eltari, Cemorokandang, Kecamatan Kedungkandang, Kota Malang - Ahmadi Kgs; Lorine Tantalu; Nonok Supartini; Edyson Indawan; Imroatus Sholiqah (Jurnal Pemberdayaan Masyarakat, 2021)
The Eltari Waste Bank is one of the Malang Waste Banks under the guidance of the Malang City Environment Service. Located at Jalan Palmerah RT 02 RW 06, Cemorokandang, Kedungkandang District, Malang City, it provides a place for the process of collecting waste that has been sorted based on conditions and types of waste, both organic and non-organic. Not all residents have understood the importance of sorting waste by type, coupled with the not yet optimal use of non-organic or plastic waste to become goods needed by the community. Through the waste management assistance process by the service team in the form of the introduction of efforts to recycle plastic packaging waste into mats and bags, it is able to increase the productivity of the Eltari Waste Bank. The introduction activity succeeded in attracting the interest of residents around the Waste Bank because in addition to being able to increase the livelihoods of local residents, it can also increase family income up to 25%.